Analysis of Satisfaction Index in the Community Application of Indonesian Program Elements Healthy in the regional puskesmas Health office work Pekanbaru city (JURNAL PROTEKSI KESEHATAN, 2021)
The Indonesia Sehat program is implemented to improve the degree of public health through health efforts and community empowerment supported by financial protection and equitable health services. The implementation of the Healthy Indonesia program is organized through a family approach. The purpose of this study was to analyze community satisfaction in implementing the elements of a healthy Indonesia program in the Pekanbaru City Health Center Work Area. This research is descriptive correlation with cross sectional analytic design. The research sample of 346 respondents with a purposive sampling method. The results of the univariate analysis showed the value of the community satisfaction index in the implementation of the Healthy Indonesia Program in the Work Area of ​​the Pekanbaru City Health Office, which was 3.014 with a conversion value of 75.36. This means that the quality of service provided to patients falls into category B (good). Statistically, there is a relationship between PISPK service elements and community satisfaction in the working area of ​​Peknbaru City Health Center in 2019. It is recommended that institutions improve the quality of human resources through training programs and seminars in order to increase the competency and capacity of officers.